2018
DOI: 10.4103/jfmpc.jfmpc_348_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of sexual health disorders among adult men in a rural area of North India: An observational study

Abstract: Background and Objectives:Sexual health disorders are an important but less researched public health issue in India. We aimed to estimate the prevalence of sexual health disorders and their associated factors among adult men in a rural community of Haryana, India.Materials and Methods:A community-based cross-sectional study was conducted among adult men aged 18–60 years using a multistage stratified random sampling. Information pertaining to sociodemographic characteristics, lifestyle and sexual practices, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…A total of 65.4% (n = 36) of the patients in our study were married as against 34.5% (n = 19) who were never married. Similar finding is seen in other community and hospital-based studies 9,[12][13][14] in India. In our study, 29.0% (n = 16) had no sexual partners during last 6 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A total of 65.4% (n = 36) of the patients in our study were married as against 34.5% (n = 19) who were never married. Similar finding is seen in other community and hospital-based studies 9,[12][13][14] in India. In our study, 29.0% (n = 16) had no sexual partners during last 6 months.…”
Section: Discussionsupporting
confidence: 91%
“…On assessment of sexual complaints, 37.7% (20 out of 53 patients) had 2 or more psychosexual disorders occurring together. In our study, maximum patients were found to have PME, alone or in combination, whereas in community-based study 14 in North India, self-perceived defects in semen, loss of libido, and masturbation guilt were much more prevalent than PME and ED. In community-based study in South India, 6 ED (15.8%) was found to be most common than PME (8.8%).…”
Section: Discussioncontrasting
confidence: 56%
“…Sexual Rehabilitation of Cancer patients at least one sexual dysfunction. Multiple sexual problems were present in 14% of the participants with more prevalent loss of libido and premature ejaculation in participants aged > 30 years [4].…”
Section: A R T I C L E I N F O a B H I J E E T D H A W A L R A M F A Y Ementioning
confidence: 99%
“…This multidimensional process encompasses the self-acceptance of one's gender identity or sexual orientation and the consequential revelation of this self-realization with others, a "profoundly personal and intricate experience." 1 This journey may commence at any point in life, from adolescence to adulthood, and the subsequent responses received, notably from family, significantly affect an individual's mental and emotional health. 2 However, these responses can vary extensively, from rejection to acceptance.…”
Section: Family Acceptance and Mental Health In Lgbtqia+ Individuals:...mentioning
confidence: 99%